A Study of Role Clarity and Need for Clarity for Three Occupational Groups - Ivancevich, John M.; Donnelly, James H. (Academy of Management Journal, 1974)
Role clarity and the need for role clarity are investigated empirically as interpreted by a total of 261 salesmen, supervisors, and operating employees in a medium-size electronic manufacturing plant. It was found that a high need for clarity moderates the relationship between role clarity and a number of variables for the three occupational groups.